Prognostic value of intracranial seizure onset patterns for surgical outcome of the treatment of epilepsy. Issue 2 (February 2015) - Jiménez-Jiménez, Diego; Nekkare, Ramesh; Flores, Lorena; Chatzidimou, Katerina; Bodi, Istvan; Honavar, Mrinalini; Mullatti, Nandini; Elwes, Robert D.C.; Selway, Richard P.; Valentín, Antonio; Alarcón, Gonzalo
Highlights Focal fast activity at onset was associated with favourable postsurgical outcome. Diffuse electrodecremental event at onset was associated with poor outcome. A preceding focal, widespread or bilateral epileptiform discharge was not associated with either favourable or poor outcome.